Training-Induced Adaptations: A Comparative Study of Aerobic Capacity, Muscular Endurance, and Cricket-Specific Performance in Adolescent Athletes - Tanveer Ali; Vikas Saxena (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This study investigates training-induced adaptations in aerobic capacity, muscular endurance, and cricket-specific performance among adolescent athletes aged 13–18 years. A randomized controlled trial was conducted with 60 male and female cricketers assigned to three groups: aerobic training (AT), resistance training (RT), or combined training (CT) for 12 weeks. Aerobic capacity was assessed via VO2max testing, muscular endurance through push-up and plank tests, and cricket-specific performance via batting accuracy, bowling speed, and fielding agility drills. Results indicated significant improvements in VO2max (p < 0.01) for the AT group compared to RT, with CT showing moderate gains. Muscular endurance improved significantly in the RT and CT groups (p < 0.05), particularly in upper-body strength. Cricket-specific performance, notably bowling speed and fielding agility, showed the greatest improvement in the CT group (p < 0.01), suggesting synergistic effects of combined training. No significant differences were observed in batting accuracy across groups. These findings highlight the efficacy of tailored training protocols in enhancing physiological and sport-specific outcomes in adolescent cricketers. The results have implications for designing age-appropriate training programs to optimize performance and support talent development in cricket. Further research should explore long-term adaptations and include diverse populations.